Evaluation of the early literacy program used in day care centers in Muntinlupa City - Jugo, Maria Agnes S. (2005)
The study aimed to examine the early literacy performance and achievement of the Muntinlupa Day Care children by analyzing the city's early literacy program and its contribution to the literacy development of the day care children. Instruments used were the Rating Scale, Early Childhood Environment and Teacher Observation, Teacher-Interview Checklists, and Teacher-Rating Scales. These were tested in day care centers in Muntinlupa City. The Natural Narrative Observations were added for classroom observations. It was found that the early literacy program in Muntinlupa City geared toward the traditional approach. The day care children also excel in alphabetic knowledge and syllable awareness in English and Filipino. However, there is still a lot to improve in the city's day care service when it comes to its early literacy program.
Thesis (M.A. Reading Education)--University of the Philippines, Diliman.
Keywords: Literacy programs -- Philippines -- Muntinlupa City -- Evaluation; Day care centers -- Activity programs -- Philippines -- Muntinlupa City